Unleashing the full potential of relaying - Elsheikh, Elsheikh Mohamed Ahmed; Kit-Kai, Wong (2007)
Understanding the relay channel is a key to developing efficient cooperative schemes, which could significantly enhance the efficiency of a wireless network. In this study, we consider a decode-and-forward (DF) relay channel and address the resource allocation for optimal relaying.